Critical review of problem solving processes traditional theoretical models - Botía Sanabria, María Lucero (Editorial Bonaventuriana, 2018)
This paper presents a brief analysis of most known problem solving theoretical models realized using epistemological categories such as observer position, object of study, methods and procedures, and descriptive or explicative scope. The review showed linear and cyclical models, the need to recognize method´s limitations to generalizing, the relevance of expliciting observer position, and a diffuse delimitation of the object “problem solving” as a cognitive process. An integrative and molar theoretical model of problem solving as a dependent variable is proposed whose variations go with critical cognitive processes (information processing, comprehension, reasoning, cognitive styles, and attitudes). Its molar feature refers to that it integrates basic and high order processes in a general cognitive activity; this proposal has to be extensively tested.